2018
DOI: 10.1364/ol.43.001207
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound modulated laser confocal feedback imaging inside turbid media

Abstract: Ultrasound modulated laser confocal feedback technology is proposed in the imaging inside turbid media. By selecting the detectable signal photons and rejecting the background noise photons in the frequency domain based on the ultrasound modulation, the signal-to-noise ratio (SNR) can be much improved, especially in the turbid media, compared with the traditional imaging without ultrasound modulation. This is a promising method to reach both a larger penetration depth and a better SNR than other optical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, the system is also challenged to realize both high resolution and large penetration depth the same as the other optical methods. Therefore, combining other technologies with the advantages of the laser confocal feedback tomography is interesting research, such as the numerically reconstructing imaging to extend the DOF and ultrasound-modulated technology to improve the SNR [96,97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system is also challenged to realize both high resolution and large penetration depth the same as the other optical methods. Therefore, combining other technologies with the advantages of the laser confocal feedback tomography is interesting research, such as the numerically reconstructing imaging to extend the DOF and ultrasound-modulated technology to improve the SNR [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the laser confocal feedback imaging is also affected by the scattered photons [39], and the generated speckles reduce the image contrast as well as the SNR. To solve the problem, Zhu [97] applied the ultrasound-modulated technology in the laser confocal feedback imaging. The system is shown in Figure 26.…”
Section: Ultrasound Modulated Laser Confocal Feedback Imagingmentioning
confidence: 99%
“…Using FUS at different stimulation levels, authors not only observed 10 times higher signal-to-noise ratio (Zhu et al, 2018) for 1064 nm luminescent laser but also increased sensitivity or better spatial resolution. The best resolution was reported at 2 mm (Ahmad et al, 2017;Klein et al, 2018) using 640 nm laser or 18 F lasers.…”
Section: Fus-cl In Turbid Microenvironmentsmentioning
confidence: 99%
“…In order to mimic tissue environments, agarose phantom is usually used as it has similar scattering coefficient as that of native tissues following Monte Carlo model (Wang et al, 1995). Since native tissues may vary from species to species, phantoms typically have a scattering coefficient from 1 to 80 cm −1 (Kobayashi et al, 2016;Ahmad et al, 2017;Zhu et al, 2018). Through phantoms, transparent silicon tubes were run at different depths.…”
Section: Fus-cl In Turbid Microenvironmentsmentioning
confidence: 99%
See 1 more Smart Citation